Buckberg versus Calafiore Cardioplegia in Patients with Acute Coronary Syndromes - Kuhn, Elmar W.; Liakopoulos, Oliver; Slottosch, Ingo; Deppe, Antje Christin; Choi, Yeong-Hoon; Madershahian, Navid; Wahlers, Thorsten C. W. (The Thoracic and Cardiovascular Surgeon, 2018)
Background Choice of cardioplegic solution plays a pivotal role in special subgroups of patients referred for on-pump cardiac surgery. This retrospective analysis aimed to assess the impact of intermittent warm (Calafiore, Cala) versus intermittent cold blood cardioplegia (Buckberg, Buck) in patients referred to coronary artery bypass graft (CABG) surgery due to acute coronary syndromes (ACS).Methods From 2008 to 2015, all consecutive patients undergoing urgent on-pump CABG surgery due to ACS (n = 950) were retrospectively analyzed. Intraoperative cardiac arrest was achieved using Buck (n = 273) or Cala (n = 677). Patients were compared regarding clinical outcomes and perioperative myocardial injury (PMI). Propensity score matching was performed to control for differences in preoperative patient characteristics.Results Prevalences of left main stenosis >50%, COPD, and advanced New York Heart Association (NYHA) class were higher for intermittent warm blood cardioplegia (IWC)-patients while more Buck-patients had preoperative intra-aortic balloon pump (IABP) and redo procedures. Buck-patients needed more intraoperative defibrillations and showed longer cardiopulmonary bypass (CPB) and aortic clamping times. 30-day all-cause mortality (10.6 versus 9.3%), major adverse cardiac events (MACE) (52.7 versus 48.6%), and PMI (50.5 versus 55.7%; all p > 0.05) rates were comparable for Buck- and Cala-patients. Propensity score matching resulted in equal group sizes (n = 212 each) and balanced distribution of preoperative covariates. Although more Buck-patients still needed inotropic support >24 hours postoperatively (25.7 versus 14.7%; p = 0.005) compared with Cala-group, outcome variables of interest did not differ between treatment groups (30-day mortality: 7.5 versus 9.0%; MACE: 49.5 versus 40.6%; PMI: 48.1 versus 37.3%; all p > 0.05).Conclusion Buckberg and Calafiore cardioplegia offer comparable myocardial protection and similar postoperative results in patients undergoing CABG surgery due to ACS.
Keywords: myocardial protection/cardioplegia; cardiopulmonary bypass; CPB; coronary artery bypass grafts surgery; CABG